Cold water immersion as a post-exercise recovery strategy - Kaczmarek, M.; Mucha, D.; Jarawka, N. (Medicina Sportiva, 2013)
The demands of professional sport are growing rapidly, as well as the work load at practice. Applying the right way of physical therapy in a right moment and correctly specified time is a significant problem for coaches and athletes in many sports. To shorten the recovery time between practices or competitions, new ways of post-practice recovery techniques are being researched. One of them is the ice bath therapy and its beneficial effect on muscles changes induced by physical effort. Used after hard workouts or competitions, it is supposed to: support recovery, decrease the muscle pain and shorten the time for body to go back to the state before workouts. This review tries to summarize the findings of international research, as well as tries to explain the different results of those findings. This article reviews research, that shows positive impact of cold water immersion on post-exercise recovery.